Answer:
sin A = sin B = sin C
Explanation:
The sine rule is a law which relates all the three sides of a triangle with the sine of their opposite angles in the triangle. Given a triangle with a side of a and an opposite angle of A, side b with opposite angle B and side c with opposite angle C. The sine rule is given as:
![(sin(A))/(a)=(sin(B))/(b)=(sin(C))/(c)](https://img.qammunity.org/2022/formulas/mathematics/college/3erf06t2a0nglinu9co8f7l12u72j055ki.png)
Given that all the side of the triangle have a length of 1, that is a = b = c = 1, hence the equation becomes:
![(sin(A))/(1)=(sin(B))/(1)=(sin(C))/(1)\\\\sin(A)=sin(B)=sin(C)](https://img.qammunity.org/2022/formulas/mathematics/college/uilkwhsadflx9qtv72m3g1yfw611yoa3jj.png)